2016
DOI: 10.1242/jcs.180885
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 regulates the dynamics of lytic granules in cytotoxic T lymphocytes

Abstract: HDAC6 is a tubulin deacetylase involved in many cellular functions related to cytoskeleton dynamics, including cell migration and autophagy. In addition, HDAC6 affects antigen-dependent CD4 + T cell activation. In this study, we show that HDAC6 contributes to the cytotoxic function of CD8 + T cells. Immunization studies revealed defective cytotoxic activity in vivo in the absence of HDAC6. Adoptive transfer of wild-type or Hdac6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
(40 reference statements)
0
37
1
Order By: Relevance
“…HDAC6-silenced CD4 T cells showed a similar hyper-acetylation of tubulin than taxol-treated cells and even higher centrosome polarization than control cells ( 90 ). Likewise, in HDAC6-deficient CD8 T cells, the polarization of the centrosome is also higher than in control cells (it is closer to the IS) and tubulin acetylation is increased ( 91 ). Taxane (paclitaxel and docetaxel) binding to MTs was mapped to the β-tubulin subunit on the MT inner surface ( 92 ); the initially accepted model proposed that taxanes and other MT-stabilizing agents reach the binding pocket by diffusing through the MT wall.…”
Section: The Is and Its Axonemal Connectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…HDAC6-silenced CD4 T cells showed a similar hyper-acetylation of tubulin than taxol-treated cells and even higher centrosome polarization than control cells ( 90 ). Likewise, in HDAC6-deficient CD8 T cells, the polarization of the centrosome is also higher than in control cells (it is closer to the IS) and tubulin acetylation is increased ( 91 ). Taxane (paclitaxel and docetaxel) binding to MTs was mapped to the β-tubulin subunit on the MT inner surface ( 92 ); the initially accepted model proposed that taxanes and other MT-stabilizing agents reach the binding pocket by diffusing through the MT wall.…”
Section: The Is and Its Axonemal Connectionsmentioning
confidence: 99%
“…In fact, the knockout mouse for Kif5b , the KHC involved, is embryonic lethal, showing perinuclear clustering of lysosomes and mitochondria. Kinesin-1 is helped in the transport of lytic granules to the IS by the action of HDAC6 ( 91 ). In HDAC6 knockout T cells, the acetylation of MTs is highly increased, but the centrosomal polarization to the IS of either silenced CD4 or knockout CD8 T cells was even enhanced ( 90 , 91 ).…”
Section: Motoring the Synaptic Organelles To Fuel Cytoskeletal Dynamimentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for HDAC6-enhanced T cell-mediated cytotoxicity is that CTLs are highly motile cells and require a dynamic cytoskeleton to actively approach potential target cells, whereas inhibition of HDAC6 is known to reduce cell migration. A recent study has demonstrated that HDAC6 is an effector of the immune cytotoxic response that acts by affecting the dynamics, transport and secretion of lytic granules by CTLs [116]. Taken together, the works summarized above demonstrate that HDAC6 is an essential component of autophagy-based immune response and an effector of the CTL response to viral infection.…”
Section: Controlling Antiviral Immune Responsesmentioning
confidence: 82%